2001
DOI: 10.1042/cs1010021
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue thickness affects in vivo quantitative near-IR spectroscopy in human skeletal muscle

Abstract: A B S T R A C TThe influence of adipose tissue thickness (ATT) on near-IR spectroscopy (NIRS) measurements in vivo was studied in the human flexor digitorum superficialis muscle at rest and during sustained isometric handgrip exercise. NIRS was used for the quantitative measurement of muscle O 2 consumption (mV c O 2 ) and forearm blood flow (FBF) in 78 healthy subjects. Skinfold thickness ranged from 1.4 to 8.9 mm within the group. Resting mV c O 2 was 0.11p0.04 ml of O 2 :min − 1 :100 g − 1 , and FBF was 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(188 citation statements)
references
References 24 publications
8
178
2
Order By: Relevance
“…The mean value for m _ V VO 2 (O 2 Hb) was 22AE2% and the withinsubject variability ranged from 5AE4 to 45AE0%. This is in agreement with Kragelj et al (2000) who found a group CV of 21AE8% for m _ V VO 2 calculated from Hb diff and with our previous study (Van Beekvelt et al, 2001b) where we found a CV of 16AE2% within one test session. During exercise, the group CV was roughly the same for both methods.…”
Section: Methods Mvosupporting
confidence: 94%
“…The mean value for m _ V VO 2 (O 2 Hb) was 22AE2% and the withinsubject variability ranged from 5AE4 to 45AE0%. This is in agreement with Kragelj et al (2000) who found a group CV of 21AE8% for m _ V VO 2 calculated from Hb diff and with our previous study (Van Beekvelt et al, 2001b) where we found a CV of 16AE2% within one test session. During exercise, the group CV was roughly the same for both methods.…”
Section: Methods Mvosupporting
confidence: 94%
“…In this context, adipose tissue thickness is known to additionally affect the measurement of mO 2 , as the path of the light is different in adipose tissue compared with muscle tissue. Hence, a high amount of subcutaneous fat will result in an underestimation of mO 2 35 . However, as this study is based on a repeated within-subject measure design, effects of tissue thickness variability should not have any influence on the presented results.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the adipose tissue thickness the results from the caliper measurements were divided by two 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore an alternative explanation is a differential blunting of the near-infrared signal between groups due to the effects of subcutaneous adipose tissue thickness at the site of interrogation. Since fat acts as a low-scattering constant absorber of near-infrared light an increased subcutaneous fat thickness has the potential to blunt the interrogative depth of near-infrared light into the interrogated tissue and therefore reduce the detectable change in haemoglobin oxygenation in response to exercise (Bhambhani 2004;Van Beekvelt et al 2001). …”
Section: [Hhb] Kineticsmentioning
confidence: 99%